EFFECT OF COMPENSATION, MOTIVATION AND TRAINING ON EMPLOYEE WORK PRODUCTIVITY (Case Study on PT. Kimia Farma Trading and Distribution Cirebon) - Jajuk Herawati; Epsilandri Septyarini; Adefia Ramadona (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2023)
This research was conducted with the aim the effect of compensation, motivation and training on Work Productivity. The population in this study are employee of PT. Kimia Farma Trading and Distribution Cirebon, with a sample of 67 employee of PT. Kimia Farma Trading and Distribution Cirebon as respondents. Data was collected using the questionnaire method. The test results in this study are Compensation has a positive effect on Employee Work Productivity, Motivation has no effect on Employee Work Productivity, Training has a positive effect on Employee Work Productivity